Strategi Menjaga Eksistensi Kearifan Lokal Sasi dalam Pengelolaan Sumber Daya Laut di Era Disrupsi - Pangestu, Aji; Erni Mulyanie (Indonesian Journal of Glasial Geography, 2024)
Indonesia is a country that has the largest biodiversity in the world and has a variety of local wisdom which contains various meanings. Local wisdom is an important sector that must be preserved by the people of Indonesia, one of the local wisdoms is the Sasi local wisdom in Maluku where local wisdom has been carried out for a long time and has the aim of managing and protecting natural resources both in the sea and on land. This research aims to find out the strategies to maintain the existence of Sasi local wisdom in managing marine resources in the era of disruption, the Sasi local wisdom studied is in Adaut Village, Selaru Sub-district, West Southeast Maluku Regency. This research uses the literature study method, namely by collecting various sources that are related to the themes and topics discussed. The data that has been obtained afterwards is analysed using descriptive methods. The results of this study are that the Adaut village community has long applied Sasi local wisdom in an effort to protect and manage marine resources so as to provide benefits to meet the needs of the community at this time and for the next generation, strategies that can be done to maintain the existence of Sasi local wisdom in the disruption era are by maximising the role of formal education in schools that emphasise local culture-based education, the community includes youth in Sasi local wisdom activities, and the community collaborates with the government to provide guidance to the community to continue to maintain the extension of Sasi local wisdom.